2016
DOI: 10.1016/j.joca.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Does pre-surgical central modulation of pain influence outcome after total knee replacement? A systematic review

Abstract: The aim of this study is to systematically review whether the presence of altered central pain modulation pre-surgical influences outcome after total knee replacement (TKR) in patients with knee osteoarthritis (OA), and if so which indices of central pain modulation predict poor outcome after TKR. To identify relevant articles, PubMed and Web of Science were searched. The search strategy was a combination of key words related to "Knee Osteoarthritis and Total Knee Replacement", "Central Pain Modulation" and "P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 60 publications
4
70
0
Order By: Relevance
“…The association between duration of symptoms and CPM has particular clinical implications. CPM can be assessed easily in a clinical setting and can predict treatment outcomes including that of TKA . Moreover CPM may respond to rehabilitation, such as the joint mobilization intervention evaluated in our previous study .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The association between duration of symptoms and CPM has particular clinical implications. CPM can be assessed easily in a clinical setting and can predict treatment outcomes including that of TKA . Moreover CPM may respond to rehabilitation, such as the joint mobilization intervention evaluated in our previous study .…”
Section: Discussionmentioning
confidence: 98%
“…Clinical trials in knee OA have demonstrated that longer pain duration has been associated with poorer outcomes . In addition, abnormal descending pain inhibition may predict poor pain outcomes after total knee arthroplasty, and women may be at increased risk for have poorer total knee arthroplasty outcomes . There are currently no validated appropriateness criterial for knee arthroplasty—moreover, women tend to delay surgery until their symptoms are more severe than their male counterparts .…”
Section: Discussionmentioning
confidence: 99%
“…A predisposition to develop neuropathic pain may be present in FBSS patients due to genetic or epigenetic factors, independent of surgical technique or patient management, but at present we cannot identify these factors pre-operatively, though genetic polymorphisms may eventually help. Patients with more and wider spread secondary hyperalgesia as well as with psychological dysfunction have a higher risk of poor surgical outcome 14, 17, 25 Whether this reflects higher susceptibility to establishment of an autonomous centralized state is intriguing to consider, but requires evidence to support it.…”
Section: Pain Mechanisms (Table 2)mentioning
confidence: 99%
“…Nonetheless, further investigation is needed to better understand the neurobiological underpinnings of these centrally mediated comorbid symptoms and how they interact with psychological variables. A recent systematic review adopted a broader approach and interpreted self‐report measures of catastrophic thinking and pain coping strategies as indices of altered central pain modulation, based on the capacity of the forebrain to modulate pain processing through powerful descending pathways . This review found strong evidence that pain coping skills and catastrophic thinking were predictors of more pain at various time points after TKA .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review adopted a broader approach and interpreted self‐report measures of catastrophic thinking and pain coping strategies as indices of altered central pain modulation, based on the capacity of the forebrain to modulate pain processing through powerful descending pathways . This review found strong evidence that pain coping skills and catastrophic thinking were predictors of more pain at various time points after TKA . Meanwhile, Brummett et al .…”
Section: Discussionmentioning
confidence: 99%